New symmetric and lattice shaped high-temperature superconducting coil cross sections - Naoya Uchiyama; Shinichi Ishiguri (Results in Physics, 2016)
To improve the performances of high-temperature superconducting (HTS) coils, it is necessary to store more energy within a shorter HTS tape length and to reduce leakage magnetic fields. To attain these goals, we need to increase the critical current of the coil. The critical currents and n-values of the HTS tape generally depend on the magnitudes and angles of the applied magnetic field. Therefore, we calculated the transport current performances of HTS coils with anisotropic properties. In general, anisotropy generates relatively large electric fields at the coil edges, limiting the transport current performances of the coil. To solve this problem, we proposed a new symmetric, lattice shaped HTS coil cross sections. The coil assembly consists of small ring-shaped coils of rectangular cross section forming pairs of Helmholtz coils. As a result, the angle between the magnetic field and tape and electric fields decreased, resulting in an increase in the critical current of the coil. Through this optimization, the stored energy increased 2.2 times compared with a normal rectangular solenoid coil with the same HTS tape length. Furthermore, the leakage magnetic field was substantially reduced. Keywords: Symmetric and lattice shaped coil cross sections, Critical current, Stored energy, Leakage magnetic fields